Foliate papillitis: A cause of oral cancerophobia! - Satya Ranjan Misra; Abhishek Banerjee; Rupsa Das; Satya Sundar Gajendra Mahapatra (Oral Oncology Reports)
Foliate papillae are a cluster of multiple tiny projections that are arranged in transverse folds on the postero-lateral border of the tongue anterior to the palatoglossal fold present bilaterally. There is a lack of awareness amongst healthcare workers regarding the same, adding to the dilemma, and if misdiagnosed as malignant, it has a big psychological impact. Hence it is imperative to highlight this benign condition in the literature to enable correct diagnosis and eliminate cancerophobia.